2020
DOI: 10.1029/2020ja028250
|View full text |Cite
|
Sign up to set email alerts
|

OI 630.0‐nm and N2 1PG Emissions in Pulsating Aurora Events Observed by an Optical Spectrograph at Tromsø, Norway

Abstract: We performed observations of pulsating aurora (PsA) with an optical spectrograph at Tromsø, Norway, during wintertime in 2016-2017. The data analysis of multiple PsA events revealed the PsA spectra for the first time. As the results, the OI 630.0-nm emissions and the N 2 1PG emissions were found in the both spectra during brighter (ON) and darker (OFF) phases in the PsA events. The spectra of pulsations were derived as difference spectra between the ON and OFF spectra. From the obtained spectra of pulsations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The 630 nm PsA's patch, whose shape was similar to that of the 558 nm PsA, also brightened, as shown in Figures 3f and 3h. Regarding the WMI-630-observed PsAs, this type of on-off modulation (or main pulsation) could have been mainly dominated by N 2 1 PG (10,7) (not by OI 630 nm), as suggested by Tsuda et al (2020). By contrast, their observations also showed OI 630 nm emission as a component of the stable or background emission (or the not-pulsating component).…”
Section: Case 1: 0-4 Ut On 18 February 2018mentioning
confidence: 87%
See 3 more Smart Citations
“…The 630 nm PsA's patch, whose shape was similar to that of the 558 nm PsA, also brightened, as shown in Figures 3f and 3h. Regarding the WMI-630-observed PsAs, this type of on-off modulation (or main pulsation) could have been mainly dominated by N 2 1 PG (10,7) (not by OI 630 nm), as suggested by Tsuda et al (2020). By contrast, their observations also showed OI 630 nm emission as a component of the stable or background emission (or the not-pulsating component).…”
Section: Case 1: 0-4 Ut On 18 February 2018mentioning
confidence: 87%
“…It is generally strange for OI 630 nm emissions to pulsate, as shown in Figures 3e-3h since their lifetime is 110 s. The OI 630 nm pulsation might have been caused at a lower altitude than a typical emission altitude by quasi-periodic soft electron precipitation, as suggested by Liang et al (2016). Further analysis, such as that conducted by Tsuda et al (2020), is necessary to identify which OI 630 nm emission or N 2 1 PG (10,7) emission contributed to the pulsation detected by the WMI-630, in future work.…”
Section: Case 1: 0-4 Ut On 18 February 2018mentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, spectral observations of PsA were reported by Tsuda et al. (2020) who demonstrated that the luminosity of the N 2 1PG emissions in the range of 600–900 nm actually pulsates during PsA. This result implies that a number of N 2 1PG band emissions beyond 600 nm have significant contributions for both the cases of RG665 and BG3 filters.…”
Section: Instrumentsmentioning
confidence: 92%